Genome-guided discovery of microbial natural products - Lee, Chung Hung (Nanyang Technological University, 2024)
Antimicrobial resistance is a problem in public health and new drugs are always needed. Natural products discovery is an important part of drug development and the genes responsible for production are often found clustered together and are known as biosynthetic gene clusters (BGCs) and most are silent under standard cultivation conditions. The products of BGCs that encode thioester reductase (TD) domain-containing polyketide synthases (PKS) or non-ribosomal peptide synthetases (NRPS) usually have novel chemical structure and interesting bioactivities. In my FYP work, six strains of actinobacteria containing cryptic TD-encoding BGC were selected, and two methods were applied to activate the silent BGCs. The first method was the use of chemical elicitors to stimulate the production of the secondary metabolites, and the second was a targeted overexpression of putative activator genes to elicit the expression of biosynthetic genes. Several compounds not found in the wild type were produced from the gene overexpression. HPLC and LC-MS analysis were conducted to obtain the UV-Vis spectra and molecular mass of these compounds, revealing that some of the compounds did not match known compounds in natural product databases. The research work laid down the foundation for further structure characterization to determine whether they are novel compounds.